Inhibition of phosphatidylinositol 3-kinase activity by association with 14-3-3 proteins in T cells. - Bonnefoy-Bérard, N (1995)
Proteins of the 14-3-3 family can associate with, and/or modulate the activity of, several protooncogene and oncogene products and, thus, are implicated in regulation of signaling pathways. We report that 14-3-3 is associated with another important transducing enzyme, phosphatidylinositol 3-kinase (PI3-K). A recombinant 14-3-3 fusion protein bound several tyrosine-phosphorylated proteins from antigen receptor-stimulated T lymphocytes. PI3-K was identified by immunoblotting and enzymatic assays as one of the 14-3-3-binding proteins in resting or activated cells. Moreover, endogenous 14-3-3 and PI3-K were coimmunoprecipitated from intact T cells. Far-Western blots of gel-purified, immunoprecipitated PI3-K with a recombinant 14-3-3 fusion protein revealed direct binding of 14-3-3 to the catalytic subunit (p110) of PI3-K. Finally, anti-phosphotyrosine immunoprecipitates from activated, 14-3-3-overexpressing cells contained lower PI3-K enzymatic activity than similar immunoprecipitates from control cells. These findings suggest that association of 14-3-3 with PI3-K in hematopoietic (and possibly other) cells regulates the enzymatic activity of PI3-K during receptor-initiated signal transduction.